MELACAK PEMIKIRAN AL-ALUSI DALAM TAFSIR RUH AL-MA’ANI - Yeni Setianingsih (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2017)
Every exegesis book has its own special characteristic in accordance with the result of Interpreter’s thinking, and every interpreter has his own tendency in accordance with  the scope of social setting. Moreover, owing to expanding science, and the more  strong of judgement from interpreters, more and more it makes the work of exegesis has inclination to the scientific or the science specialization in accordance with each owned ability. It is likewise happened to Al-Alûsî  in his exegesis, Rûh al-Ma’ânî. The involvement of Al-Alûsî  in mysticism field since he was child, also makes his exegesis has sufismystic nuance. Nevertheles, ra’yi’s substance is still felt strong in his exegesis. The way of his work in interpreting the holy Qur’an certainly is not apart from his first idea about the concept of Qur’an, tafsir, and ta’wîl. Because of the explaining about the three trams, it can be known what it makes Al-Alûsî ’s criterion in interpreting the holy Qur’an.   Keywords: Al-Alûsî , Rûh al-Ma’ânî, sufismystic.